Alterations in neural Theory of Mind processing in euthymic patients with bipolar disorder and unaffected relatives. (15th December 2015) - Willert, Anna; Mohnke, Sebastian; Erk, Susanne; Schnell, Knut; Romanczuk‐Seiferth, Nina; Quinlivan, Esther; Schreiter, Stefanie; Spengler, Stephanie; Herold, Dorrit; Wackerhagen, Carolin; Romund, Lydia; Garbusow, Maria; et al.
Abstract : Objectives: Behavioral deficits in the Theory of Mind (ToM) have been robustly demonstrated in bipolar disorder. These deficits may represent an intermediate phenotype of the disease. The aim of this study was: (i) to investigate alterations in neural ToM processing in euthymic patients with bipolar disorder, and (ii) to examine whether similar effects are present in unaffected relatives of patients with bipolar disorder suggesting that ToM functional activation may be, in part, due to genetic risk for the disease. Methods: A total of 24 euthymic patients with bipolar disorder, 21 unaffected first‐degree relatives, and 81 healthy controls completed a ToM task while undergoing functional magnetic resonance imaging. Results: We observed reduced bilateral activation of the temporoparietal junction (TPJ) and diminished functional fronto‐temporoparietal connectivity in patients compared to controls. Relatives tended towards intermediate temporoparietal activity and functional coupling with medial prefrontal areas. There was also evidence for a potentially compensatory enhanced recruitment of the right middle temporal gyrus and stronger connectivity between this region and the medial prefrontal cortex in relatives. Conclusions: These findings provide further evidence of altered neural ToM processing in euthymic patients with bipolar disorder. Further, our findings in relatives lend support to the idea that altered ToM processing may act as an intermediate phenotype of the disorder.